RANCANG BANGUN TEMPAT PENYIMPAN BENIH KEDELAI (GLYCINE MAX (L) MERR) SEDERHANA - Yulia Pratiwi; Ni Luh Sri Suryaningsih; Yosefina Mangera (Faculty of Agriculture, Musamus University, 2020)
The purposes of this research get a place was to the depository the soybean seed which simple and easly used by farmers. This tool is expected to suppres the rate of deteriorasi and to solve the problem of the avaibilty for seeds in the growing season. Based on the testing of a depository the soybean seed airtight and ashes husks as the adsorbent can suppress the rate of deteriorasi. Viabilitas that is used to stored the soybean seed on the moon first month is 66,4%, second month 51,8% and the third month 13,6%. Viabilitas in which is kept in a sack is 32,4% and viabilitas went down to 0% in the 2nd and 3rd. Vigor seeds that are stored in the depository seed place on the first month is 1,67% larger than vigor, for the second month to third month than on the seeds of which are kept using the sacks. The average temperatur 28,3 and Rh 86,6% with long keeping 1 month produce the result of growing is better than with the humidity space save equal and long time. The form of a place for depository of the soybean seed is a tube with a measure of 25 cm height and diameter of 15 cm. Volume used is 3469,7 load the soybean seed varieties Anjasmoro as many as 2,5 kg.